2021
DOI: 10.1101/2021.03.08.21252775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High levels of common cold coronavirus antibodies in convalescent plasma are associated with improved survival in COVID-19 patients

Abstract: Background COVID-19 Convalescent plasma (CCP) is safe and effective, particularly if given at an early stage of the disease. Our study aimed to identify an association between survival and specific antibodies found in CCP. Patients and Methods Patients >18 years of age who were hospitalized with moderate to severe COVID-19 infection and received CCP at the MD Anderson Cancer Center between 4/30/2020 and 8/20/2020 were included in the study. We quantified the levels of anti-SARS-CoV-2 antibodies, as wel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The findings illustrate that extraneutralizing effector functions of S2 stem bnAbs may be important and need to be investigated to determine their role in viral suppression or clearance. Indeed, recent studies have revealed that cross-reactive antibodies to endemic CoVs could serve as a marker for survival after severe disease (81,82) or protection against COVID-19 (83).…”
Section: Discussionmentioning
confidence: 99%
“…The findings illustrate that extraneutralizing effector functions of S2 stem bnAbs may be important and need to be investigated to determine their role in viral suppression or clearance. Indeed, recent studies have revealed that cross-reactive antibodies to endemic CoVs could serve as a marker for survival after severe disease (81,82) or protection against COVID-19 (83).…”
Section: Discussionmentioning
confidence: 99%
“…Annual circulation of common coronaviruses (cCoV) gives rise to broad cross-coronavirus immunity. However, how this cCoV-specific immunity influences the disease trajectory of COVID-19 remains unclear (39)(40)(41)(42)(43)(44)(45)(46). Among the cCoV, the β-coronavirus OC43 circulates annually in the USA (47).…”
Section: Common Coronavirus Responses Are Enriched In Survivors Early In Infection Coursementioning
confidence: 99%
“…These findings may also imply convalescent plasma collections (e.g., CCP units with greater NL63 antibody responses and lower HKU1 antibodies) had higher neutralizing antibodies to the SARS-CoV-2 receptor-binding domain (RBD) [ 38 ]. Another study found better outcomes in recipients of CCP units with higher anti-NL63 or anti-OC43 antibodies [ 39 ]; Influenza virus A(H 3 N 2 ) : Antibody binding to an epitope region from SARS-CoV-2 nucleocapsid, termed Ep9, is associated with greater COVID-19 disease severity [ 40 ]. Bioinformatics analysis identified the neuraminidase protein (not present in the influenza vaccine) of influenza virus A(H3N2) as responsible, a strain that circulated widely in 2014 [ 41 ]; Acute malaria infection: Plasmodium infection induces cross-reactive antibodies to carbohydrate epitopes on the SARS-CoV-2 spike protein [ 42 ]; Natural ABO isoagglutinins: The ABO blood group affects COVID-19 incidence and severity, as well as the type and duration of the cellular immune response [ 43 ].…”
Section: Potential Beneficial Factors In Ccpmentioning
confidence: 99%
“…These findings may also imply convalescent plasma collections (e.g., CCP units with greater NL63 antibody responses and lower HKU1 antibodies) had higher neutralizing antibodies to the SARS-CoV-2 receptor-binding domain (RBD) [ 38 ]. Another study found better outcomes in recipients of CCP units with higher anti-NL63 or anti-OC43 antibodies [ 39 ];…”
Section: Potential Beneficial Factors In Ccpmentioning
confidence: 99%